The Role of Gen Z in the 2024 Erau Festival of the Kutai Ing Martadipura Sultanate - Aisar Diva GAYATRI; Dita DISMALASARI (International Journal of Environmental, Sustainability and Social Science, 2025)
This study aims to analyze the role of Generation Z as digital marketers and active consumers in increasing the turnover of economic transactions at the Erau Festival of the Kutai Ing Martadipura Sultanate in Tenggarong, East Kalimantan. This phenomenon is interesting because the Erau Festival is not only a means of cultural preservation, but also a driver of the local economy through community participation, especially the younger generation. This study uses a mixed methods approach with a sequential explanatory design, which combines quantitative and qualitative analysis. Primary data was collected through a survey of 272 Generation Z respondents using purposive and quota sampling techniques. Data analysis was carried out using the multiple linear regression (OLS) method with the help of SPSS. The results showed that the variables Digital Marketer (B = 0.294; p < 0.001) and Active Consumer (B = 0.234; p < 0.001) had a positive and significant effect on the turnover of economic transactions, with an R² value of 0.561. This means that 56.1% of transaction turnover variations can be explained by the role of Generation Z, while the rest are influenced by other factors such as government support and cultural appeal. These findings confirm that Generation Z plays a strategic role in strengthening the culture-based creative economy through digital activities and direct consumption. Therefore, policies are needed that encourage collaboration between the local government, the Sultanate of Kutai, and the Generation Z community in the development of digital promotion, creative marketing training, and sustainable cultural economic facilitation.